Combination therapy for obesity. (November 2017) - Wilding, John PH
Obesity is a chronic disease with serious consequences and although lifestyle modification is considered first line treatment, it is often ineffective, especially in the long term. Relatively few people with obesity will undergo the most effective currently available treatment of bariatric surgery. Pharmacotherapy can bridge the gap between lifestyle modification and surgery, but many monotherapies have only modest efficacy or require high doses with unacceptable side effects. As with many other areas of medicine, combination therapy is now becoming accepted as a way of optimising efficacy for weight management, whilst minimising adverse effects. Combinations may use different medications with complementary modes of action. Currently available combination therapies are low-dose phentermine and sustained release topiramate and naltrexone/bupropion. Many other possibilities exist and promising options include combination of phentermine with a sodium glucose co-transporter 2 inhibitor or combination of a glucagon-like peptide 1 agonist with other gut hormones or with a sodium glucose co-transporter 2 inhibitor. The ultimate aim is to match the efficacy of bariatric surgery with a combination of medicines, but this remains an elusive goal.